Nanoscale Photonics and Optoelectronics Science and Technology - Wang, Zhiming M.; Neogi, Arup.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
The intersection of nanostructured materials with photonics and electronics shows great potential for clinical diagnostics, sensors, ultrafast telecommunication devices, and a new generation of compact and fast computers. Nanophotonics draws upon cross-disciplinary expertise from physics, materials science, chemistry, electrical engineering, biology, and medicine to create novel technologies to meet a variety of challenges. This is the first book to focus on novel materials and techniques relevant to the burgeoning area of nanoscale photonics and optoelectronics, including novel, hybrid materials with multifunctional capabilities and recent progress in the understanding of optical interactions in nanoscale materials and quantum-confined objects. Leading experts provide a fundamental understanding of photonics and the related science and technology of plasmonics, polaritons, quantum dots for nanophotonics, nanoscale field emitters, near-field optics, nanophotonic architecture, and nanobiophotonic materials. Key Features: Provides a comprehensive review of the fundamental knowledge of nanometer-scale light-matter interactions with emphasis on new principles and technologies. Describes applications to photonics, bioengineering, nanofabrication, information technology, and communications. Bridges between electronics and photonics by including novel hybrid materials with multifunctional capabilities.
Spontaneous Emission Control in a Plasmonic Structure -- Surface Plasmon Enhanced Solid-State Light-Emitting Devices -- Polariton Devices Based on Wide Bandgap Semiconductor Microcavities -- Search for Negative Refraction in the Visible Region of Light by Fluorescent Microscopy of Quantum Dots Infiltrated into Regular and Inverse Synthetic Opals -- Self-Assembled Guanosine-Based Nanoscale Molecular Photonic Devices -- Carbon Nanotubes for Optical Power Limiting Applications -- Field Emission Properties of ZnO, ZnS, and GaN Nanostructures -- Growth, Optical, and Transport Properties of Self-Assembled InAs/InP Nanostructures.
Keywords: Engineering; Electronics; Optical materials; Nanotechnology; Materials Science; Nanotechnology; Optics, Optoelectronics, Plasmonics and Optical Devices; Electronics and Microelectronics, Instrumentation; Optical and Electronic Materials; Nanotechnology and Microengineering; Laser Technology, Photonics